Documentary Evidence about the Relationships of the Russian and Romanian Orthodox Churches during the Years of Chairmanship of Metropolitan Nikodim (Rotov) in the Department for External Church Relations - Sergey L. Zvonarev, archpriest (Вестник Екатеринбургской духовной семинарии)
This article is intended to acquaint the reader with the content and nature of the relationship between the Russian and Romanian Orthodox Churches in the 1960s and early 1970s, when the Department for External Church Relations was headed by Metropolitan Nikodim (Rotov). The research is based primarily on materials from church and Russian state archives, as well as other official sources. A significant contribution to strengthening contacts between the Moscow and Romanian Patriarchates was made by meetings and communication at the level of primates, hierarchs and official church representatives. Mutual visits of delegations made it possible to get acquainted with church life in the Soviet Union and Romania. A high degree of coordination of the actions of the two sides could be seen in the sphere of inter-Orthodox and inter-Christian relations, and the Christian peace movement. It is noteworthy that during the studied period, the position of the Romanian Church was distinguished not only by its great openness to ecumenical contacts, which was also demonstrated by other Local Churches, in particular the Moscow Patriarchate, but by its readiness to commemorate non-Orthodox representatives during divine services. This position aroused criticism from Orthodox participants in the celebration of the 20th anniversary of the enthronement of Patriarch Justinian of Romania in 1968 in Bucharest. The academic sphere has become a promising area of cooperation between the two Churches. The education of students of the Romanian Church at the Moscow and Leningrad Theological Academies strengthened the foundations of future bilateral ties. The organization of the educational process in theological schools of the Russian Church served as a model for reforming seminary education in Romania. Various assistance and help from the Moscow Patriarchate in relation to the Romanian Church emphasized the fraternal spirit of Moscow. The author of the article comes to the conclusion that a high level of interaction on the international front has been achieved between the Russian and Romanian Churches. This made it possible to strengthen not only bilateral church contacts, but also to maintain relations between the USSR and the Socialist Republic of Romania during the period of cooling and tension, and to develop friendly ties between the Soviet and Romanian peoples.